2015
DOI: 10.4238/2015.december.1.31
|View full text |Cite
|
Sign up to set email alerts
|

LITAF, HHEX, and DUSP1 expression in mesenchymal stem cells from patients with psoriasis

Abstract: ABSTRACT. Psoriasis is a common chronic relapsing inflammatory skin disease, in which mesenchymal stem cells (MSCs) have been hypothesized to play an important role in abnormal localized inflammation and vascular proliferation observed in skin lesions. Previous studies have revealed abnormal gene expression patterns, DNA methylation status, and cytokine secretion of MSCs in psoriatic skin lesions, as well as some gene expression abnormalities related to inflammation and angiogenesis. We further verified the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Dermal MSCs were isolated and expanded as described in previous studies (Hou et al, 2014, Chang et al, 2015. Non-adherent cells were removed after 48 h, and half the medium was changed every 3-4 days.…”
Section: Culture and Characterization Of Dermal Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermal MSCs were isolated and expanded as described in previous studies (Hou et al, 2014, Chang et al, 2015. Non-adherent cells were removed after 48 h, and half the medium was changed every 3-4 days.…”
Section: Culture and Characterization Of Dermal Mscsmentioning
confidence: 99%
“…We have previously reported that some inflammation-and angiogenesis-related genes, such as IL-1β, CXCL14, VEGFα, GATA-6, insulin-like growth factor-binding protein-5 (IGFBP5), lipopolysaccharide-induced tumor necrosis factor-alpha transcription factor (LITAF), and dual-specificity protein phosphatase 1 (DUSP1), are significantly differentially expressed in dermal MSCs from patients with psoriasis (Liu et al, 2013;Hou et al, 2014;Chang et al, 2015). Psoriatic dermal MSCs present an impaired capacity to inhibit T cell proliferation (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A two‐step method was adopted to separate DMSCs. First, the skin samples were cut into small pieces of approximately 1 mm, which were then digested using 0.25% Dispase enzyme II (Sigma, St. Louis, MO, USA) at 4 °C overnight. Second, the epidermis and dermis were separated using mechanical methods, and the dermis was then minced.…”
Section: Methodsmentioning
confidence: 99%
“…After 72 hours, the culture medium was changed to remove the cells in suspension. Then, half of the old culture medium was replaced with fresh medium every 3 days . We harvested the 5th generation of cells to identify whether these cells were DMSCs .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation